A narrative review on clinical trials showing contraindicated drugs with grapefruit juice (Sciences of Phytochemistry, 2023)
Medication and food are frequently consumed together. However, some foods have interactions with medicines by changing key regulators of systemic medication availability. Their consumption is linked to interactions with a wide range of medications. One of the most significant beverages that can be harmful when combined with certain medicines is grapefruit juice. Furanocoumarins' mechanism-based suppression of intestinal cytochrome P450 3A4, which increases the bioavailability of drugs that are substrates, is the main mechanism by which interactions are mediated. There have also been reports of interactions between grapefruit products and uptake transporters such as P-glycoprotein (P-gp) and organic anion-transporting polypeptides (OATPs). It has been suggested that polyphenolic substances like flavonoids are what cause the interactions between P-gp and OATP. The amounts of furanocoumarins and flavonoids in the grapefruit product, the amount of juice consumed, the medium PH, and the inherent diversity of enzymes and transporter components in humans can all have an impact on the processes and magnitudes of interactions. In this review, we are going to shed light on clinical trials showing grapefruit juice-drug interactions and what should the health provider do for better clinical care.